Fluency Disorders : Current Practices and Perspectives of Speech-Language Pathologists - Loch, Kelsey; Tweten, Megan; Sterling-Orth, Angela; Thistle, Jennifer (My University, 2017)
The purpose of this study was to identify the speech-language pathologists' (SLPs) perspectives and knowledge of treating fluency disorders, as well as identifying the need for continuing education resources for fluency disorders.
Color poster with text, graphs, and images.
Keywords: Fluency disorders; Speech-language pathologists; Stuttering; Posters